105 The Epigenetics and Plasticity of CD4+ T Cells in Poultry Health. (8th October 2021) - Song, Jiuzhou; He, Yanghua; Ding, Yi; Tian, Fei; Zhao, Keji; Zhang, Huanmin; Yu, Ying; Yang, Ning; Lian, Ling; Luo, Juan; Mitra, Apratim
Abstract: Marek's disease (MD) is one of the top priority diseases in chicken. The mechanisms through which immune cells react to virus infection and pathway signals represent the fundamental cell biological question to defeat MD. We hypothesized epigenetic status in immune organs and cells is directly associated with how the Marek's disease virus (MDV) infection influences intrinsic transcriptional and regulatory networks in MD. To investigate the epigenetics in CD4+ T cells induced by MDV infection, we assembled a multifaceted approach with epigenetics, deep sequencing, and computational methods together to explore the roles of epigenetics in unique inbred lines of chickens. First, a genome-wide transcriptome analysis in the immune organs from resistant line 63 and susceptible line 72 chickens was performed to explore disease resistance mechanisms. MDV infection influences both cytokine-cytokine receptor interaction and cellular development in resistant and susceptible chickens. Second, we examined the epigenetic status of CD4+ T cells induced by MDV infection, including DNA methylations, histone modifications, chromatin accessibility, and 3D chromatin structures. Our results revealed more than 5, 000 epigenetic modification changes (FDR< 0.01) and methylation changes (>15, 000, FDR< 0.01) caused by MDV infection. Only resistant line 63 chickens could initiate robust adaptive immune responses at the transcription level (>200 genes, FDR< 0.05). The increase in chromatin accessibility (P < 0.001) and chromosome reorganization represented by A/B compartment flipping were related to up-regulated genes induced by MDV infection ten days post-infection in line 63 chickens. Our findings provided a deeper insight into the CD4+ T cell commitment and responses toward viral infection. In particular, the identifications of cis-acting and trans-acting regulations and lipid pathways will improve our understanding of the sequence, structural basis of RNA-protein, and RNA-DNA interactions and serve as the impetus for mechanistic studies to refine the genomic and epigenetic control of MD resistance in poultry.